Gene Expression Modulation in Bovine Endometrial Cells Infected with Gammaherpesvirus Type 4 and Exposed to Lipopolysaccharide in the Presence of Platelet-Rich Plasma - Lopez, Sofia; Álvarez, Ignacio; Andreoli, V.; Delgado, S.; Pérez, S.; Pereyra, Susana Beatriz; Romeo, Florencia; Grolli, S.; Verna, Andrea Elizabeth (MDPI, 2025)
Uterine diseases in cattle are frequently linked to bacterial infections, with pathogens commonly isolated from the uterine lumen. Bovine Gammaherpesvirus Type 4 (BoGHV-4) is notably prevalent in certain regions of Argentina and is associated with uterine diseases in postpartum cattle. This study aims to evaluate the impact of platelet-rich plasma (PRP) on the gene expression related to BoGHV-4 infection in the presence of lipopolysaccharide (LPS), exploring the potential of PRP as a therapeutic alternative. The interaction between LPS and Toll-like receptor 4 (TLR4) plays a crucial role in inflammatory responses, triggering cytokine production and immune activation. Our results show that PRP modulates TLR4 and TNF-α gene expression, indicating a potential inhibitory role in inflammatory processes. Furthermore, PRP alter the temporal dynamics of BoGHV-4 replication by modulating the expression of the viral immediate–early gene (IE-2) and delaying proinflammatory cytokine responses such as IL-8. Notably, PRP enhances IFN-γ expression, which could help prevent tissue damage caused by bacterial and viral coinfection. These findings highlight the potential of PRP as an anti-inflammatory agent with therapeutic benefits in treating uterine diseases, offering an alternative to traditional antibiotic treatments.